Gastric Epithelial Expression of IL-12 Cytokine Family in Helicobacter pylori Infection in Human: Is it Head or Tail of the Coin? - Al-Sammak, Fadi; Kalinski, Thomas; Weinert, Sönke; Link, Alexander; Wex, Thomas; Malfertheiner, Peter (PLoS ONE, 2013)
Recently, there has been a growing interest in an expanding group of cytokines known as "IL-12 family". The so far gained knowledge about these cytokines, as crucial playmakers in mucosal immunity, has not yet been sufficiently investigated in the context of Helicobacter pylori infection. All genes encoding the monomeric components of these cytokines and their corresponding receptors were examined in gastric epithelial cell lines (AGS and MKN-28) after being infected with 4 H. pylori strains: BCM-300, P1 wild-type, and P1-derived isogenic mutants lacking cytotoxin-associated gene A (cagA) or virulence gene virB7 (multiplicity of infection=50). Both infected and uninfected samples were analyzed after 24h and 48h using real-time quantitative polymerase chain reaction (RT-qPCR). Gene expression analysis demonstrated a strong upregulation of IL23A (encodes p19) by infection, whereas IL23R, Epstein-Barr virus-induced gene 3 (EBI3), IL6ST, IL12A, and IL27RA were found to be expressed, but not regulated, or to a lesser extent. Transcripts of IL12RB2, IL12B, IL12RB1, and IL27A were not detected. Interestingly, P1 resulted in stronger alterations of expression than CagA mutant and BCM-300, particularly for IL23A (59.7-fold versus 32.4- and 6.7-fold, respectively in AGS after 48h, P<.05), whereas no changes were seen with VirB7 mutant. In a proof-of-principle experiment, we demonstrated epithelial-derived expression of IL-12, p19, and Ebi3 in gastric mucosa of gastritis patients using immunohistochemistry (IHC). Unlike IL-12 and Ebi3, increased immunostaining of p19 was observed in H. pylori gastritis. Herein, we highlight the potential role of gastric epithelial cells in mucosal immunity, not only because they are predominant cell type in mucosa and initial site of host-bacterial interaction, but also as a major contributor to molecules that are thought to be primarily expressed by immune cells so far. Of these molecules, p19 was the most relevant one to H. pylori infection in terms of expression and localization. © 2013 Al-Sammak et al.
CRIS-Team Scopus Importer:2025-10-13